PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 SAKRA BARAT TAHUN PELAJARAN 2016/2017 - Sabrun, Sabrun (Media Pendidikan Matematika, 2017)
The subjects of this study are students of class VIII A which amounted to 35 people. This classroom action research consists of 2 cycles, each cycle consisting of the planning stage, action implementation, observation, and reflection. Based on the result of observation analysis of student activity on cycle I meeting I got total score and average as much 37 and 2.31 categorized "Simply Active", meeting II increased to 42 and 2,63 "Active" category. While in the second cycle of meeting I the total score and the average of 48 and 3.00 categorized "Active", at the second meeting increased to 60 and 3.75 with the category "Highly Active". For the results of the analysis of teacher activity in the first cycle of meeting I obtained the total score and the average of 16 and 3.20, the second meeting increased to 18 and 3.60 with the category "Good". While in the second cycle of meeting I obtained the total score and the average of 19 and 3.80, the second meeting increased to 20 and 4.00 with the category of "Very Good". Furthermore, the students' classical learning completeness in the first cycle is 51.43% and in cycle II increases to 85.71%. So it can be concluded that the implementation of active learning model type Everyone Is A Teacher Here can improve the learning outcomes of students of class VIII SMP Negeri 1 Sakra Barat lesson 2016/2017.